REGULATORY AND SUPERVISORY TECHNOLOGY RESEARCH: A BIBLIOMETRIC ANALYSIS - Fachsandy, Faturrahman (Bank Indonesia, 2025)
This bibliometric study examines articles on Supervisory Technology (SupTech) and Regulatory Technology (RegTech). The investigation’s main focus was on author trends and keywords. The data was carefully examined from the sources indexed on Dimension.ai, where ‘SupTech’ and ‘RegTech’ were the search terms. A bibliometric map was derived using VOSviewer for bibliometric analysis and a descriptive statistical method. VOSviewer software was used to analyse the development trends of publications related to RegTech and Supertech. In recent years, there has been a sharp increase in the number of papers published on RegTech and SupTech. Various journals have tackled the subject, two of the best being “Fintech and RegTech: Impact on Regulators and Banks” by Ioannis Anagnostopoulos and “The Role of Big Data, Machine Learning, and AI in Assessing Risks: A Regulatory Perspective” by Scott W. Bauguess. The most frequently used terms include regulation, supervision, compliance, finance, and technology. Furthermore, over the past ten years, Douglas W. Arner and Simone Di Castri have authored the most articles of any authors. Challenge and Study are two of this theme’s most commonly cited keywords. Digitalisation is critical today and presents a challenge for practitioners and researchers. Academics working in RegTech and SupTech can find relevant information in this study, which gives an overview of keyword trends and the most popular scholars on the subject.